Peri-implantitis management by resective surgery combined with implantoplasty and Er:YAG laser irradiation, accompanied by free gingival graft: a case report - Takahiko Shiba; Keiji Komatsu; Takayasu Watanabe; Yasuo Takeuchi; Takashi Nemoto; Yujin Ohsugi; Sayaka Katagiri; Masahiro Shimogishi; Eriko Marukawa; Takanori Iwata (SAGE Publishing, 2023)
The optimal method for decontamination of implant surfaces for peri-implantitis treatment remains controversial. In recent years, erbium-doped yttrium aluminum garnet (Er:YAG) laser irradiation and implantoplasty (IP) (i.e. mechanical modification of the implant) have been reported to be effective in decontaminating implant surfaces during the surgical treatment. Also, a lack of adequate keratinized mucosa (KM) around the implant is known to be associated with more plaque accumulation, tissue inflammation, attachment loss, and mucosal recession, increasing the risk of peri-implantitis. Therefore, free gingival graft (FGG) has been recommended for gaining adequate KM around the implant. However, the necessity of acquiring KM for the treatment of peri-implantitis using FGG remains unclear. In this report, we applied the apically positioned flap (APF) as resective surgery for peri-implantitis treatment in conjunction with IP and Er:YAG laser irradiation to polish/clean the implant surface. Furthermore, FGG was conducted simultaneously to create additional KM, which increased the tissue stability and contributed to the positive results. The two patients were 64 and 63 years old with a history of periodontitis. The removal of granulation tissue and debridement of contaminated implant surfaces were performed with Er:YAG laser irradiation post flap elevation and then modified smooth surfaces mechanically using IP. Er:YAG laser irradiation was also utilized to remove the titanium particles. In addition, we performed FGG to increase the width of KM as a vestibuloplasty. Peri-implant tissue inflammation and progressive bone resorption were not observed, and both patients maintained good oral hygiene conditions until the 1-year follow-up appointment. Bacterial analysis via high-throughput sequencing revealed proportional decreases in bacteria associated with periodontitis ( Porphyromonas , Treponema , and Fusobacterium ). To the best of our knowledge, this study is the first to describe peri-implantitis management and bacterial change before and after procedures by resective surgery combined with IP and Er:YAG laser irradiation for peri-implantitis treatment, accompanied by FGG for increasing KM around the implants.